ANALISIS KELAYAKAN NUTRIEN ANORGANIK JENIS N, P, DAN Si UNTUK KEHIDUPAN FITOPLANKTON DI PERAIRAN PESISIR TOMPOTANA TAKALAR SULAWESI SELATAN - Rahmadi Tambaru; Abdul Haris; Muh Farid Samawi; Ilmiyanti Aulya Luthfiyah (Teknik Lingkungan Universitas Islam Indonesia, 2023)
Abstract Inorganic nutrient types such as nitrates (N), phosphates (P), and silicates (Si) are widely absorbed by phytoplankton. All three types of nutrients are very important for their growth. Through the process of photosynthesis, the three nutrients are converted into food reserves in the form of organic compounds such as carbohydrates. The results of the photosynthesis process are used by other organisms in the tropics to grow. The purpose of this study was to analyze the distribution of inorganic nutrients of type N (nitrate), P (phosphate), and Si (silicate) for phytoplankton life. The research was carried out from June to October 2021 at three stations in the coastal waters of Tompotana, Tanakeke Islands District, Takalar Regency, South Sulawesi. At the three stations, water sampling was carried out for the purposes of phytoplankton identification and measurement of physico-chemical parameters of the waters. Activities carried out in the laboratory such as phytoplankton identification, nitrate, phosphate and silicate measurements. Based on the analysis of variance, nitrate and phosphate concentrations were not significantly different (p > 0.05) between stations, on the contrary silicate concentrations actually differed significantly (p < 0.05). N, P, and Si nutrients can still be absorbed and used by phytoplankton to grow even though they are not optimal. A total of 4 classes and 24 types of phytoplankton were identified. The four classes in question are Bacillariophyceae, Dinophyceae, Cyanophyceae, and Coscinodiscophyceae. From the results of the Pearsons correlation analysis, only nitrates had a significant effect on phytoplankton abundance in Tompotana waters (p<0.05).